Anomalous thunderstorm process in the Stavropol Krai - Z. M. Kerefova; N. V. Yurchenko; A. A. Adzhieva (Наука. Инновации. Технологии)
The paper analyzes the dynamics of such anomalous weather phenomenon as a thunderstorm. The thunderstorm process that took place in the North Caucasus on June 27, 2023 is considered. The thunderstorm process under consideration differed significantly from the statistical average, both in duration and in lightning parameters. The analysis was carried out using the example of the Stavropol Krai, although anomalous thunderstorms on June 27, 2023 also occurred in other regions of the North Caucasus.The work used the lightning direction network of the Federal State Budgetary Institution VGI with spatially separated sensors LS8000 and LS7002. To determine the characteristics of thunderstorm activity, the work used long-term data from the specified lightning direction network. Studies of thunderstorm activity were carried out in conjunction with the characteristics of convective clouds determined by MRL-5 weather radars. The Federal State Budgetary Institution VGI has organized the uptake, processing, archiving and transmission to the ASPD network of Roshydromet of radar information from all MRL-5 weather radars of the anti-hail services of the North Caucasus.During the day, about 30,000 lightning strikes were recorded by VGI in this territory. Of these, 3,713 were ground discharges. Of the registered 3,713 ground-based lightning discharges in the Stavropol Krai, negative lightning amounted to 2,901, and the positive one – 812. The share of negative lightning discharges from the total number of ground-based lightning discharges in the specified territory was 78%. The largest number of negative lightning (more than 70%) had values up to 20 kA. More than 40% of positive lightning discharges had values from 21 to 40 kA. The average value of currents of negative polarity was -18.6 kA, and that of positive polarity was +53.2 kA.